Stresses analysis in semi-elliptic leaf spring and comparison with the SAE J788 (1982) norm - Daré Neto, Luiz [UNESP]; Bianchi, Eduardo Carlos [UNESP]; Fernandes, Odilson Coimbra; Filho, José Roberto Curitiba (SAE International, 2002)
In this work are presented the values found with the experimental testing, in the semi-elliptic leaf spring, utilizing 24 strain gages, distributed in five leaves of springs; these values have been compared to the calculated values found with the application of Norm SAE J788 (1982). The results showed discrepancy between the values measured and calculated and that the Norm is not indicated to determine the actuating stress in any point of any leaf of the leaf spring, but due to its simplicity and quickness of the process it presents good precision for the pre-development of the product. Copyright © 2002 Society of Automotive Engineers, Inc.
Keywords: leaf spring; semi-elliptic springs; stress analysis; Calculated values; Experimental testing; Exhibitions; Stress analysis; Leaf springs